Evaluating the Rank of Performance of Countries of the Middle East and North Africa with MADM - Ashourian, Mahboubeh (Journal of Informatics and Mathematical Sciences, 2012)
Over the past few decades, countries of Middle East and North Africa (MANA) have achieved varying levels of economic development. In this paper, Multiple Attribute Decision Making (MADM) is employed to study the rank of performance of selected MENA countries. MADM problem is a management science technique, which is popularly used to rank the priority of alternatives with respect to their computing attributes. this paper indicated that the MENA countries achieved higher values of desirable attributes and lower values of undesirable attributes.